EFFICIENT APPLICATIONS AND ARCHITECTURE OF MODERN DIGITAL SIGNAL PROCESSORS - Hartmann Tolić, Ivana; Rimac-Drlje, Snježana; Hocenski, Željko (Journal of Energy Technology, 2024)
Digital signal processors have found their roles in various fields of science and technology. With the appearance of problems related to the processing of large quantities of data in real time, it was nec-essary to develop a system that would execute procedures very rapidly and at low cost. The most common application in real time is the digitization and mathematical processing of audio, video, tem-perature, and voltage data, etc., resolved using parallel operations. Various producers of digital signal processors have developed processors and evaluation models that enable developers to quickly andefficiently create unique applications in communications and visual systems, biomedicine, meteorology, etc. In this article, the basic performance and architecture of the modern digital signal processorare described in detail with emphasis on the most common applications. A practical example of the use of a digital signal processor for numerical integration is presented. A comparison with commonlyused processors is performed to confirm its efficiency..